2010
DOI: 10.1271/bbb.90727
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic and Antimutagenic Effects of the Traditional Herb Used for Treating Erectile Dysfunction,Butea superbaRoxb.

Abstract: Butea superba is a traditional tuberous Thai plant enriched with flavonoids that is used for treating erectile dysfunction. We investigated the mutagenic and antimutagenic potentials of a B. superba extract by using the pre-incubation method of the Ames test. Salmonella typhimurium strains TA 98 and TA 100 were applied as the tester strains in the presence and absence of an S9 mixture. Prior to the mutagenic and antimutagenic tests, the survival of the tester strains was measured by treating with the B. superb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In recent years, studies have confirmed that Pue can be used to prevent and treat postmenopausal osteoporosis, showing an estrogen-like effect while being less toxic (19,20). Its ability to activate blood circulation and dissipate blood stasis has certain applications in the clinical treatment of DM (21)(22)(23). Osteoporosis is associated with degenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have confirmed that Pue can be used to prevent and treat postmenopausal osteoporosis, showing an estrogen-like effect while being less toxic (19,20). Its ability to activate blood circulation and dissipate blood stasis has certain applications in the clinical treatment of DM (21)(22)(23). Osteoporosis is associated with degenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the use of Butea superba root as a traditional medical herb hints its safety, its safety has not been rigorously evaluated. Several toxicological studies revealed that the dried roots were mutagenic at high doses in mice, and caused increases in spleen weight and increases in the levels of several blood parameters in rats . One case report described hyperandrogenemia that occurred in a male who took capsules containing Butea superba tuber for several weeks .…”
Section: Methodsmentioning
confidence: 99%
“…Several human clinical trials have been performed to prove the efficacy of Butea superba tubers for the treatment of erectile dysfunction and as an aphrodisiac, but the results led to conflicting conclusions and placebo effects were not assessed in these clinical trials. Several toxicological studies revealed that the dried roots were mutagenic at high doses in mice, 5 and caused increases in spleen weight and increases in the levels of several blood parameters in rats. Several toxicological studies revealed that the dried roots were mutagenic at high doses in mice, 5 and caused increases in spleen weight and increases in the levels of several blood parameters in rats.…”
mentioning
confidence: 99%
“…A solution containing 10% sulfuric acid dissolved in methanol. [15] RESULTS AND DISCUSSION Thin-layer chromatography (TLC) was conducted to determine the quantity of components present in the individual extracts. Various solvent systems with varying polarities were tested, and the most optimal solvent system, which yielded the highest resolution, was chosen.…”
Section: Detecting Reagentmentioning
confidence: 99%